Perception of Coexistence Measures by Farmers in Five European Union Member States. (April 2016) - Tillie, Pascal; Dillen, Koen; Rodríguez‐Cerezo, Emilio
Summary: Farm‐level coexistence measures between GM and non‐GM crops are essential to ensure the freedom of choice of both farmers and consumers that is the cornerstone of European policy in this matter. However, it is important that coexistence measures do not tip the balance against GM crops, and distort farmers' decisions on whether or not to grow these. Based on a farm survey conducted in 2012, this article analyses the perceptions of the burden of coexistence measures by farmers. A total of 1, 403 farmers were interviewed in five Member States of the EU. Results illustrate that farmers perceive coexistence measures that imply a restriction of their freedom of choice as the most burdensome, while they are less affected by practical coexistence measures in the fields or by administrative rules. Liability for damage to non‐GM farmers is also considered extremely burdensome due to the unpredictable outcome of potential litigation. However, according to the survey, few conflicts have arisen because of coexistence issues with neighbouring farmers. The burden of practical, farm‐level coexistence measures also varies across countries, depending on agro‐ecological conditions. This calls for the design of flexible, context‐specific coexistence measures, possibly complemented by non‐production constraining administrative rules. Abstract : Farm‐level coexistence measures between GM and non‐GM crops are essential to ensure the freedom of choice of both farmers and consumers that is the cornerstone of European policy in this matter. However, it is important that coexistence measures do not tip the balance against GM crops, and distort farmers' decisions on whether or not to grow these. Based on a farm survey conducted in 2012, this article analyses the perceptions of the burden of coexistence measures by farmers.